The results of research at the Zhailautobe settlement in the Talas Valley in 2023 - Onggaruly Акан; Buranbayev Руслан; Arynov Куаныш; Shagirbayev Мамбет (Turkic Studies Journal, 2024)
Kangyu settlements of the «tobe with a platform» type are known in the Talas Valley. They appeared at the turn of the millennium and represent the first sites of early agricultural culture in the area. These settlements consist of two parts: the main mound with a flat top and an adjacent section with a lower platform. The Chol-tobe and Kzyl-Kainar-tobe settlements were investigated in the 1960s. Excavations at the Bak-Tobe site were conducted from 2015 to 2019 and in 2022-23.Monumental cross-shaped and square structures were found. In 2023, the Margulan Institute of Archaeology conducted the first excavations at the Zhailautobe settlement. An excavation with a total area of 73 square metres was carried out on the lower platform. No intact structures were found, but a collection of pottery and osteological material was recovered. A stratigraphic trench revealing massive adobe structures was found on the main upper mound. The pottery from the site has numerous parallels in the sedentary agricultural settlements of the Talas Valley and southern Kazakhstan. Bone analysis in an archaeozoology lab allowed to identify species and calculate quantitative statistics. On the basis of the research results, the settlement was dated to the Late Kangyu period of the II-IV centuries.